Differences between Current Clinical Practice and Evidence-Based Guideline Recommendations Regarding Tocolysis – an Austria-wide Survey - Enengl, Sabine; Rath, Werner; Kehl, Sven; Oppelt, Peter; Mayr, Andreas; Stroemer, Annika; Eichinger, Teresa; Lastinger, Julia; Stelzl, Patrick (Geburtshilfe und Frauenheilkunde, 2024)
To evaluate the adherence of Austrian obstetricians to national guideline recommendations by investigating data on the current practice of tocolysis regarding indications, timing and monitoring of tocolysis, choice of tocolytics and serious side effects, maintenance tocolysis, support of decision-making and recommendations at patient’s discharge from the hospital.78 obstetric departments in Austria were invited to participate in a nationwide survey between June 5th and August 31st 2023 by answering a web-based questionnaire about clinical standards. The survey was conducted approximately one year after implementation of the AWMF Guideline “Prevention and Therapy of Preterm Birth” 015‑025. Collected data were analyzed descriptively by performing measures of frequency. Fisher’s exact test was used for group comparison.The response rate was 69.2% (33.3% perinatal centers, 66.7% standard care). The most important indication of tocolysis were ≥ 4 contractions within 20 minutes of CTG tracing, as stated by 26 (48.1%) of the respondents; the AWMF Guideline 015‑025 (2022) was the most important decision-making support for tocolytic treatment (61.1%). 19 (35.2%) of obstetric units started tocolysis earliest at 23 + 0 weeks of gestation. Atosiban was the first-line tocolytic drug used by 43 (79.6%) of obstetric units, followed by nifedipine (n = 7, 13.0%); 49 of 54 obstetric units (90.7%) stated to perform maintenance tocolysis, among these 46 (93.9%) not routinely but on special indications (e.g. placenta previa). Serious side effects were observed by 77.8% of the respondents, mostly associated with the use of hexoprenaline.Our survey revealed considerable discrepancies between evidence-based guideline recommendations and daily clinical practice in Austrian hospitals.
Keywords: preterm birth; tocolysis; survey; clinical practice; guideline recommendations